Public Participation, Science and Society Tools for Dynamic and Responsible Governance of Research and Innovation - Rask, Mikko (Taylor & Francis, 2018)
The field of public participation is developing fast, with phenomena such as citizen science and crowdsourcing extending the resource base of research, stimulating innovation and making science more accessible to the general population. Promoting public participation means giving more weight to citizens and civil society actors in the definition of research needs and in the implementation of research and innovation. As yet, there is limited understanding of the implications of widespread use of public participation and as a result, there is a risk that it will become a burden for research and an obstacle to bridging the gap between research and society. This volume presents the findings of a three-year international study on innovative public participation. The resulting work studies the characteristics and trends of innovative public participation through a global sample of 38 case studies. It provides theoretical generalisations on the dynamics of public participation, suggestions for an evaluation framework and clear empirical examples of how public participation works in practice. Illustrated by best practice cases, the authors identify characteristics which contribute to successful public participation. The book is aimed primarily at scholars and practitioners of public participation, as well as research managers, policy makers and business actors interested in related issues. There is also a secondary market for students and scholars of European governance studies, sociology and political sciences.